Fructose-mediated AGE-RAGE axis: approaches for mild modulation - Semchyshyn, Halyna (Frontiers in Nutrition, 2024)
Fructose is a valuable and healthy nutrient when consumed at normal levels (≤ 50 g/day).However, long-term consumption of excessive fructose and elevated endogenous production can have detrimental health impacts. Fructose-initiated nonenzymatic glycation (fructation) is considered as one of the most likely mechanisms leading to the generation of reactive species and the propagation of nonenzymatic processes. In the later stages of glycation, poorly degraded advanced glycation products (AGEs) are irreversibly produced and accumulated in the organism in an age-and diseasedependent manner. Fructose, along with various glycation productsespecially AGEsare present in relatively high concentrations in our daily diet. Both endogenous and exogenous AGEs exhibit a wide range of biological effects, mechanisms of which can be associated with following: 1) AGEs are efficient sources of reactive species in vivo, and therefore can propagate nonenzymatic vicious cycles and amplify glycation; and 2) AGEs contribute to upregulation of the specific receptor for AGEs (RAGE), amplifying RAGE-mediated signaling related to inflammation, metabolic disorders, chronic diseases, and aging. Therefore, downregulation of the AGE-RAGE axis appears to be a promising approach for attenuating disease conditions associated with RAGE-mediated inflammation. Importantly, RAGE is not specific only to AGEs; it can bind multiple ligands, initiating a complex RAGE signaling network that is not fully understood. Maintaining an appropriate balance between various RAGE isoforms with different functions is also crucial. In this context, mild approaches related to lifestylesuch as diet optimization, consuming functional foods, intake of probiotics, and regular moderate physical activityare valuable due to their beneficial effects and their ability to mildly modulate the fructose-mediated AGE-RAGE axis.